A radiation quality correction factor kQ for well‐type ionization chambers for the measurement of the reference air kerma rate of 60Co HDR brachytherapy sources. Issue 7 (22nd June 2015) - Schüller, Andreas; Meier, Markus; Selbach, Hans‐Joachim; Ankerhold, Ulrike
Abstract : Purpose: The aim of this study was to investigate whether a chamber‐type‐specific radiation quality correction factor kQ can be determined in order to measure the reference air kerma rate of 60 Co high‐dose‐rate (HDR) brachytherapy sources with acceptable uncertainty by means of a well‐type ionization chamber calibrated for 192 Ir HDR sources. Methods: The calibration coefficients of 35 well‐type ionization chambers of two different chamber types for radiation fields of 60 Co and 192 Ir HDR brachytherapy sources were determined experimentally. A radiation quality correction factor kQ was determined as the ratio of the calibration coefficients for 60 Co and 192 Ir. The dependence on chamber‐to‐chamber variations, source‐to‐source variations, and source strength was investigated. Results: For the PTW T x 33004 (Nucletron source dosimetry system (SDS)) well‐type chamber, the type‐specific radiation quality correction factor kQ is 1.19. Note that this value is valid for chambers with the serial number, SN ≥ 315 (Nucletron SDS SN ≥ 548) onward only. For the Standard Imaging HDR 1000 Plus well‐type chambers, the type‐specific correction factor kQ is 1.05. Both kQ values are independent of the source strengths in the complete clinically relevant range. The relative expanded uncertainty ( k = 2) of kQ is U k Q = 2.1% for both chamber types. Conclusions: The calibration coefficient of a well‐type chamber for radiation fields of 60 Co HDR brachytherapy sources can be calculated from a given calibration coefficient for 192 Ir radiation by using a chamber‐type‐specific radiation quality correction factor kQ . However, the uncertainty of a 60 Co calibration coefficient calculated via kQ is at least twice as large as that for a direct calibration with a 60 Co source.